203k views
1 vote
Math
Match the answers

Math Match the answers-example-1

1 Answer

1 vote

Answer:

No solution

Infinitely many solutions

One solution

Explanation:

The first expression:

-2(3x - 1) = -6x -1

Expand the parentheses;

-6x + 2 = -6x -1

-6x + (-6x) = -1 -2

0 = -3

This problem has no solutions

Second expression:

2(3x-1) = 6x -2

Expand the parentheses;

6x - 2 = 6x -2

6x -6x = -2 + 2

0 = 0

This problem has infinitely many solutions

Third expression:

2(3x - 1) = -6x -2

Expand the parentheses;

6x -2 = -6x - 2

6x + 6x = -2 + 2

12x = 0

x = 0

This equation has only one solution

User Inox
by
5.3k points